The Role of Authentic Leadership in Achieving Organizational Prosperity : An Analytical Study of the Opinions of Managers in the Housing Sector Organizations / Kurdistan Region of Iraq - Ismael, Dr. Hadi Kh.; Saeed, Haife H. (Mitanni Journal of Humanitarian Sciences, 2023)
The study sought to reveal the role of authentic leadership represented by its dimensions (self-awareness, transparency of relationships, internal ethical perspective, and balanced processing of information) in achieving organizational prosperity expressed by its dimensions (innovation, intellectual capital, and sustainable competitive advantage). The descriptive analytical approach was used to collect and analyze data to reach the results, as a hypothetical model was built that reflects the relationship between the variables of the study, and a questionnaire was adopted to collect data through a comprehensive survey of the study population, and the final number of respondents reached (282) from managers in the housing sector organizations / Kurdistan Region, Data analyzes were carried out using the statistical package (SPSS version 22), and linear regression analysis was used to test the hypotheses. The results showed that there is a significant impact of authentic leadership on organizational prosperity at the macro level and at the level of dimensions. Based on the conclusions, a number of recommendations were presented to enhance the levels of authentic leadership practice in the surveyed organizations and the levels of organizational prosperity in them, in addition to providing suggestions for future studies. The originality and value of the study is represented in bridging the knowledge gap resulting from the scarcity of studies that investigated the relationship between original leadership and organizational prosperity in the environment of Iraqi organizations in general, and in the housing sector organizations in particular.